Referral of intravenous drug users for antiviral treatment: effectiveness of hepatitis C case-finding programmes - Gazdag, Gábor; Horváth, Gergely; Szabó, Olga; Ungvari, Gabor S (Central European Journal of Public Health, 2012)
BACKGROUND: Hepatitis C infection (HCI) case-finding programmes aim to identify infected persons in a well-defined population. This study assessed the effectiveness of three HCI case-finding programmes for intravenous drug usersBy examining the rate of their referral to antiviral treatment. METHODS: The Hepatology Outpatient Clinic of Szent László Hospital examines and treats all intravenous drug users who are found positive in HCI case-finding programmes inBudapest. The medical records of patients who visited the Hepatology Outpatient Clinic of Szent László HospitalBetween 1 January 2006 and 31 December 2008 were screened and records indicating a history of drug abuse were selected. These records were matched against the databases of the hepatitis case-finding programmes and the records that appeared inBoth datasets were analyzed. RESULTS: Of the 234 intravenous drug users identified as hepatitis C virus positive in theBudapest case-finding programmes, only 21 attended the Hepatology Outpatient Clinic of Szent László Hospital and only two started antiviral treatment,But their hepatitis C virus positive status had alreadyBeen known at the time of screening. CONCLUSION: In this study, not a single patient with drug abuse whose hepatitis C virus positive status was identified in one of the HCI case-finding programmes was referred for antiviral treatment.
Keywords: hepatitida C; Mass Screening; zdravé chování; intravenózní abúzus drog; zdravotnické služby; Hepatitis C; lidé; Maďarsko; Substance Abuse, Intravenous; plošný screening; Health Services; Hungary; Patient Acceptance of Health Care; Health Behavior; Referral and Consultation; pacientův souhlas se zdravotní péčí; konziliární vyšetření a konzultace; Antiviral Agents; Humans; antivirové látky